Spiritual Transformation and Moral Exemplars: An Analysis of Female Figures in Qur’anic Narratives - Pratama, Yolan Hardika (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2025)
This study examines the narrative of exemplary women in the Qur’an with the aim of uncovering the moral and spiritual messages embedded in the stories of female figures and their contribution to character education among Muslims. A qualitative approach using library research and intertextual analysis was employed to synthesize findings from various literatures, including classical and contemporary studies. The results reveal that figures such as Maryam, the wife of Pharaoh, the mother of Musa, the Queen of Sheba, the “barren” women, Zulaikha, and the wives of Nuh and Luth, consistently embody values of obedience to Allah, courage, and the inner transformation that is fundamental to faith. Maryam stands out as a symbol of purity and spiritual strength, capable of receiving divine revelation directly, while the wife of Pharaoh demonstrates a personal choice to reject tyranny despite being in a repressive environment. The story of the mother of Musa illustrates sacrifice and fortitude in facing life's trials, whereas the Queen of Sheba provides an example of transformation from worldly power to profound obedience. Furthermore, the narrative of the “barren” women teaches that biological limitations do not hinder Allah's gift in creating life, and the story of Zulaikha reveals the dangers of desire as well as the potential for repentance as a path to spiritual restoration. These findings affirm that the Qur’an provides a comprehensive framework of values, emphasizing the importance of equal rights and responsibilities in building a just and dignified society.